9 things successful people do differently - Heidi Grant- Halvorson (Harvard Business Review Press, 2012)
Are you at the top of your gameor still trying to getthere?Take your cues from the short, powerful 9 Things SuccessfulPeople Do Differently, where the strategies and goals of the worldsmost successful people are on displaybacked by research that showsexactly what has the biggest impact on performance. Heres a hint:accomplished people reach their goals because of what they do, notjust who they are.Readers have called this a gem of a book. Getready to accomplish your goals at last.